2016
DOI: 10.4172/2150-3508.1000165
|View full text |Cite
|
Sign up to set email alerts
|

Inventory of Ichyofaunal Diversity, Fishing Gear and Craft in Turag River, Dhaka, Bangladesh

Abstract: Biodiversity of many Bangladesh Rivers is seriously threatened by industrial and municipal pollution. The study was conducted in the Turag River starting from Amin Bazar bridge (23°47' N 90°20'E) to Kamarpara bridge (23°53' N 90°23'E). This inventory survey was sampled at a fortnightly interval usually between 7.00 am to 5.00 pm by a team using a boat from December 2012 to November 2013. Detailed information on catch by species, fish length and weight, different types of gear and craft were collected through d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
0
2
1
Order By: Relevance
“…Diversity of fish of the present study indicated the poor status of fish diversity both qualitatively and quantitatively. On the other hand, Bhouiyan (2016) recorded 9 orders and 25 families in the Turag River which were somewhat higher than the present study [13] . Kamrujjaman and Nabi (2015) observed 18 families and 8 orders in the Bangshi River which were more or less similar to the present findings [18] .…”
Section: Resultscontrasting
confidence: 79%
See 1 more Smart Citation
“…Diversity of fish of the present study indicated the poor status of fish diversity both qualitatively and quantitatively. On the other hand, Bhouiyan (2016) recorded 9 orders and 25 families in the Turag River which were somewhat higher than the present study [13] . Kamrujjaman and Nabi (2015) observed 18 families and 8 orders in the Bangshi River which were more or less similar to the present findings [18] .…”
Section: Resultscontrasting
confidence: 79%
“…Obviously, it seems very poor condition compared to other rivers in Bangladesh and might be due to the worst water quality of river which did not support the diversified fish species. And Bhouiyan (2016) and Hossain et al (2012) reported of 71 species of freshwater fishes (65 indigenous and 6 exotic species) and 53 species of finfishes respectively from the same river which were more than the present study and some other rivers of Bangladesh [13,14] . (Bhuiyan et al, 2008; Rahman et al, 2012) [15,16] .…”
Section: Resultsmentioning
confidence: 47%
“…The rivers also support a diverse range of aquatic life, including fish species. Some research has been carried out on the ichthyofaunal diversity of these rivers includes, Baki et al (2017) reported 56 fish species under 20 families and 9 orders from Buriganga river, Bhouiyan et al (2016) reported 71 species of fish under 25 families of 9 orders from Turag River and Miah et al (2010) reported 20 species of fishes belonging to 18 genera, under 10 families from Shitalakshya river at Siddirgonj area, Narayangonj. The plans are to build a new campus for the Jagannath University at Tegharia in Keraniganj.…”
Section: Introductionmentioning
confidence: 99%